Blockade of IL‐33 signalling attenuates osteoarthritis - He, Zengliang (Clin Transl Immunology, 2020)
OBJECTIVES: Osteoarthritis (OA) is the most common form of arthritis characterised by cartilage degradation, synovitis and pain. Disease modifying treatments for OA are not available. The critical unmet need is to find therapeutic targets to reduce both disease progression and pain. The cytokine IL‐33 and its receptor ST2 have been shown to play a role in immune and inflammatory diseases, but their role in osteoarthritis is unknown. METHODS: Non‐OA and OA human chondrocytes samples were examined for IL‐33 and ST2 expression. Novel inducible cartilage specific knockout mice (IL‐33(Acan CreERT2)) and inducible fibroblast‐like synoviocyte knockout mice (IL‐33(Col1a2 CreERT2)) were generated and subjected to an experimental OA model. In addition, wild‐type mice were intra‐articularly administered with either IL‐33‐ or ST2‐neutralising antibodies during experimental OA studies. RESULTS: IL‐33 and its receptor ST2 have increased expression in OA patients and a murine disease model. Administering recombinant IL‐33 increased OA and pain in vivo. Synovial fibroblast‐specific deletion of IL‐33 decreased synovitis but did not impact disease outcomes, whilst cartilage‐specific deletion of IL‐33 improved disease outcomes in vivo. Blocking IL‐33 signalling also reduced the release of cartilage‐degrading enzymes in human and mouse chondrocytes. Most importantly, we show the use of monoclonal antibodies against IL‐33 and ST2 attenuates both OA and pain in vivo. CONCLUSION: Overall, our data reveal blockade of IL‐33 signalling as a viable therapeutic target for OA.